Whole genome MBD-seq and RRBS analyses reveal that hypermethylation of gastrointestinal hormone receptors is associated with gastric carcinogenesis - Kim, Hee-Jin; Kang, Tae-Wook; Haam, Keeok; Kim, Mirang; Kim, Seon-Kyu; Kim, Seon-Young; Lee, Sang-Il; Song, Kyu-Sang; Jeong, Hyun-Yong; Kim, Yong Sung (Experimental & molecular medicine, 2018)
DNA methylation is a regulatory mechanism in epigenetics that is frequently altered during human carcinogenesis. To detect critical methylation events associated with gastric cancer (GC), we compared three DNA methylomes from gastric mucosa (GM), intestinal metaplasia (IM), and gastric tumor (GT) cells that were microscopically dissected from an intestinal-type early gastric cancer (EGC) using methylated DNA binding domain sequencing (MBD-seq) and reduced representation bisulfite sequencing (RRBS) analysis. In this study, we focused on differentially methylated promoters (DMPs) that could be directly associated with gene expression. We detected 2,761 and 677 DMPs between the GT and GM by MBD-seq and RRBS, respectively, and for a total of 3,035 DMPs. Then, 514 (17%) of all DMPs were detected in the IM genome, which is a precancer of GC, supporting that some DMPs might represent an early event in gastric carcinogenesis. A pathway analysis of all DMPs demonstrated that 59 G protein-coupled receptor (GPCR) genes linked to the hypermethylated DMPs were significantly enriched in a neuroactive ligand–receptor interaction pathway. Furthermore, among the 59 GPCRs, six GI hormone receptor genes ( NPY1R , PPYR1 , PTGDR , PTGER2 , PTGER3 , and SSTR2 ) that play an inhibitory role in the secretion of gastrin or gastric acid were selected and validated as potential biomarkers for the diagnosis or prognosis of GC patients in two cohorts. These data suggest that the loss of function of gastrointestinal (GI) hormone receptors by promoter methylation may lead to gastric carcinogenesis because gastrin and gastric acid have been known to play a role in cell differentiation and carcinogenesis in the GI tract. Stomach cancer: DNA methylation of hormone receptor genes A sequencing study reveals abnormal changes to DNA that set the stage for stomach cancer development. DNA methylation, the addition of methyl groups to alter DNA activity, is often disrupted in human cancers. Yong Sung Kim at the Korea Research Institute of Bioscience and Biotechnology (KRIBB) in Daejeon, South Korea, and co-workers used sequencing technogy to identify critical methylation changes in stomach epithelial cells, intestinal metaplasia lesion and tumor cells during early-stage gastric cancer. The team found 3,035 abnormally methylated DNA regions related to the expression of particular genes. Further analysis identified six hormone receptor genes directly involved with stomach acid secretion, whose altered expression was linked to over-methylated DNA regions. Loss of function within these six genes may lead to gastric cancer, and their expression levels could be valuable biomarkers for the disease.